2017
DOI: 10.1001/jamainternmed.2016.6807
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Prevalence of Dementia in the United States in 2000 and 2012

Abstract: IMPORTANCEThe aging of the US population is expected to lead to a large increase in the number of adults with dementia, but some recent studies in the United States and other high-income countries suggest that the age-specific risk of dementia may have declined over the past 25 years. Clarifying current and future population trends in dementia prevalence and risk has important implications for patients, families, and government programs. OBJECTIVE To compare the prevalence of dementia in the United States in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
499
7
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 695 publications
(548 citation statements)
references
References 30 publications
39
499
7
3
Order By: Relevance
“…Cerebrovascular disease is preventable and modification of lifestyle has been recognized to have a significant impact on decreasing the incidence and prevalence of vascular disease dementia [45,46] and dementia more broadly [25]. Given that VaD had the greatest prevalence of NPS, which are the leading cause of institutionalization, there is enormous societal benefit to implementing prevention programs for vascular disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cerebrovascular disease is preventable and modification of lifestyle has been recognized to have a significant impact on decreasing the incidence and prevalence of vascular disease dementia [45,46] and dementia more broadly [25]. Given that VaD had the greatest prevalence of NPS, which are the leading cause of institutionalization, there is enormous societal benefit to implementing prevention programs for vascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, it has been suggested that ischemic small vessel disease is likely associated with psychosis in AD [24] Thus, by better understanding the underlying vascular changes that are associated with certain NPS, we can better target treatment options, arguing for more aggressive treatment for vascular disease. Langa et al [25] recently conducted a study in the USA that found a significantly decreased prevalence of dementia in the year 2012 when compared to the prevalence in 2000 for subjects aged 65 years or older. Furthermore, the authors suggest that “increasing educational attainment and better control of cardiovascular risk factors may have contributed to the improvement, but the full set of social, behavioral, and medical factors contributing to the improvement is still uncertain” [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used 27 items from this test to assign a TICS27 score [22]. Using thresholds defined in this report, we classified participants as follows: 0–6 = dementia; 7–11 = cognitive impairment not dementia; and 12–27 = normal cognition.…”
Section: Methodsmentioning
confidence: 99%
“…Prevention of AD is thus clearly the current preferred alternative [8], and national plans in many countries are encouraging higher education and healthier lifestyles. The decrease in prevalence of dementia in the United States between 2000 and 2012 is attributed primarily to an increase in educational attainment [9], and other countries are reporting reductions attributed to stricter control of vascular risk factors in mid-life. An excellent overall perspective on how to defeat dementia has been written by science writer Elie Dolgin, in his feature news [10].…”
Section: Contextmentioning
confidence: 99%